Review of the mite genus Prozercon Sellnick, 1943 (Acari: Zerconidae) in Turkish Thrace, with descriptions of four new species - Karaca, Mehmet (Zootaxa, 2025)
Soil, litter and moss samples collected from Turkish Thrace between 2012 and 2014 years, were evaluated and 18 Prozercon species were found. Among them, P. elifae sp. nov., P. esati sp. nov., P. gamzeae sp. nov. and P. tataroglui sp. nov. are described as new species. Altitude and habitat preferences of all Prozercon mites are reviewed.